2014
DOI: 10.1192/bjp.bp.113.135285
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the diagnostic changes to post-traumatic stress disorder for DSM-5 and the proposed changes to ICD-11

Abstract: The diagnostic systems performed in different ways in terms of current prevalence rates and levels of comorbidity with depression, but on other broad key indicators they were relatively similar. There was overlap between those with PTSD diagnosed by ICD-11 and DSM-5 but a substantial portion met one but not the other set of criteria. This represents a challenge for research because the phenotype that is studied may be markedly different according to the diagnostic system used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
91
5
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(128 citation statements)
references
References 22 publications
27
91
5
1
Order By: Relevance
“…In line with our hypothesis and consistent with previous findings (Carmassi et al, 2013; Elhai et al, 2009, 2012; Gentes et al, 2014; Kilpatrick et al, 2013; Miller et al, 2013; O’Donnell et al, 2014; Stein et al, 2014), no change in provisional PTSD prevalence was identified when the criteria shifted from DSM-IV to DSM-5. Although, DSM-IV and DSM-5 include a different number of qualifying symptoms, group these symptoms into specific clusters, and thus implicitly demand specific symptom characteristics to be present in a minimum number and specific combination, possibly leading to the identification of somewhat different patient populations in the present study, the agreement between both systems was satisfactory.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In line with our hypothesis and consistent with previous findings (Carmassi et al, 2013; Elhai et al, 2009, 2012; Gentes et al, 2014; Kilpatrick et al, 2013; Miller et al, 2013; O’Donnell et al, 2014; Stein et al, 2014), no change in provisional PTSD prevalence was identified when the criteria shifted from DSM-IV to DSM-5. Although, DSM-IV and DSM-5 include a different number of qualifying symptoms, group these symptoms into specific clusters, and thus implicitly demand specific symptom characteristics to be present in a minimum number and specific combination, possibly leading to the identification of somewhat different patient populations in the present study, the agreement between both systems was satisfactory.…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, only two studies to date have systematically compared all four diagnostic systems, again yielding inconsistent results. Whereas Stein et al (2014) found no differences in PTSD prevalence at all, O’Donnell et al (2014) reported no differences between DSM-5 and DSM-IV, but lower PTSD prevalence under the proposed ICD-11 compared to DSM-IV, DSM-5, and ICD-10. Notably, although interpretation of prevalence differences between different diagnostic systems is limited when no consistency is reported, analyses of agreement between the diagnostic systems are provided only by some authors (Carmassi et al, 2013; Elhai et al, 2009; Gentes et al, 2014; Kilpatrick et al, 2013; Morina et al, 2014; Stammel et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations